Uji Aktivitas Antioksidan Tiga Spesies Tanaman Sarang Semut (Famili: Rubiaceae) Asal Kabupaten Merauke, Papua - Septriyanto Dirgantara; As’ari Nawawi; Muhamad Insanu (Jurnal Biologi Papua, 2013)
Sarang semut plant is one of indigenous medicinal plants of Merauke region, the Papua province. Local people use the bulb of sarang semut plants to cure inflammation, muscle pain and enhancing immunity. However rare research of the plants has been done especially on the antioxidant activity. The objective of this research was to investigate the antioxidant activity of three species of sarang semut plants which were Myrmecodia beccarii, Myrmecodia sp. and Hydnophytum sp. The test was necessary to identify the inhibitory concentration level of plant extract in blocking a free radical (IC50). Parts of plants were extracted with maceration using methanol for 3 x 24 h to produce concentrated methanol.  Plant extracts of three species were then subject to   antioxidant activity test based on free radical blocking of 1,1-Difenil-2-Pikrilhidrazil (DPPH) qualitatively and quantitatively using Ultraviolet-Visible spectrophotometry. The results showed the methanol extract of M. beccarii, Myrmecodia sp. and Hydnophytum sp. were active as antioxidants with IC50 from 8.18 ppm, 21.79 ppm, 25.31 ppm, respectively while Vitamin C as a control has IC50 7.85 ppm. In conclusion, three  plant species of sarangsemut are potential  as natural antioxidant and plant extracts of M. beccarii showed the highest antioxidant activity among others. Key words: Antioxidant, sarang semut plants, Rubiaceae, DPPH.